Bacteriocins of lactic acid bacteria and their application on food as biopreservatives. (II) - METAXOPOULOS (Ι. ΜΕΤΑΞΟΠΟΥΛΟΣ) J.; MATARAGAS (M. ΜΑΤΑΡΑΓΚΑΣ) M.; DROSINOS (Ε.Χ. ΔΡΟΣΙΝΟΣ) E. H. (Journal of the Hellenic Veterinary Medical Society, 2017)
Lactic acid bacteria produce a variety of small molecular weight compounds, which have antimicrobial properties. Such substances are: organic acids, alcohols, carbon dioxide, diacetyl, hydrogen peroxide and bacteriocins. Many of these compounds have a wide inhibitory spectrum but the bacteriocins are able to inhibit species, namely, related with the bacteriocin-producing strain. In the last years bacteriocins have gained a lot of concern because some of them are able to inhibit the growth of pathogenic bacteria, like Listeria monocytogenes. The term "biopreservation" refers to the extension of storage life, as well as to the enhancement of the food safety, using the bacteriocin-producing lactic acid strains or their metabolic antibacterial products. In this review will be reported bacteriocins, which are produced by the lactic acid bacteria and will be discussed the potential application of the bacteriocinogenic strains or their bacteriocins on the foods, as protective cultures or as protective compounds, respectively.